PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Real Estate Dan Property Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2013) - Fitri Anita; Yesi Mutia Basri; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of corporate socialresponsibility, leverage, likuiditas dan firm size effect corporate aggresiveness tax. Type of this reseacrh is causative research. The population in this research is real estate and property company registered in BEI in 2010 until 2013. Sample was determined by the purposive sampling method. Types of data is secondary data and the method of analysis used is multiple regression analysis. The test results of this study indicate that corporate social responsibility, leverage, firm size have no effect on corporate aggressive tax. Meanwhile, liquidity effect on corporate aggresive tax. In this study, there are still many limitatios and short comings the effect of independent variables on the dependent variable can only explain by 8,3%, hence more independent variable are needed.Keywords: Corporate Social Responsibility, leverage, liquidity, firm size, and aggresive tax